The prevalence of Mycoplasma pneumoniae in children in Shandong, China before, during, and after COVID-19 - Kong, Wenna; Wang, Qianqian; Zhuo, Jinhua; Zhuang, Xuewei (Frontiers in Pediatrics, 2024)
The multifaceted non-pharmaceutical interventions after the outbreak of the COVID-19 pandemic not only limited the spread of SARS-CoV2 but also had an impact on the prevalence of other pathogens.: In this work, we retrospectively analyzed the epidemiological characteristics of Mycoplasma pneumoniae (MP) in children before and after the COVID-19 pandemic in Shandong, China. From 2019 to 2023, there were 29558 visits of pediatric patients (1 month to 15 years old) with respiratory tract infection (RTI) symptoms at a tertiary hospital in Shandong Province, 10039 of which were positive for MP according to a passive agglutination assay of the serum IgM antibodies. Conduct statistical analysis and epidemiological investigation of the test results categorized by years, months, ages, genders and clinical diagnosis. Utilize the χ 2 test to analyze the differences in incidence rates. Results: Compared to 2019, the number of visits and the positive cases both decreased substantially in 2020, but the positivity rate increased. Both 2021 and 2023 were peak years of MP infection. The peak seasons of MP infection were fall and winter, female patients had higher positivity rate than male patients, and school-age children (>6 years) had higher positivity rate than the children in other age groups. In terms of the clinical manifestation of MP infection, compared to 2019, in 2023, the proportion of bronchopneumonia and upper RTI decreased significantly. Conclusions: The ongoing surveillance of the epidemiology of MP is critical for effective disease management and provides a basis for diagnosis, treatment, and the corresponding prevention and control strategies. This work for the first time characterized the epidemiology of MP in Shandong before and after the COVID-19 pandemic, thus providing valuable information 3 for monitoring and preventing MP infection in the post-epidemic era.